Mind-blowing magic tricks for everyone : 50 step-by-step card, coin, and mentalism tricks that anyone can do - Owen, Oscar (Magician) (Skyhorse Publishing, 2021)
Packed inside this book are more than fifty astonishing magic tricks that anyone can do. Learn mystifying card tricks, awe-inspiring coin tricks, mind-reading routines, deceptive bets, and amazing visual tricks that will make you the life of the party!